2014
DOI: 10.3109/03009742.2014.881549
|View full text |Cite
|
Sign up to set email alerts
|

Mental health indicators and quality of life among individuals with musculoskeletal chronic pain: a nationwide study in Iceland

Abstract: Our data indicate that individuals with musculoskeletal chronic pain have increased risk of poor mental health and diminished QoL. Further studies are needed on treatment and preventative measures of a decline in mental health among individuals with chronic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 13 publications
3
21
1
Order By: Relevance
“…Such relationships have been found both in chronic pain cohorts and in population-based studies [75][76][77]. These cross-sectional correlations were confirmed in our study and extended also to the longitudinal aspects (Table 5), as we found significant correlations between pain intensities in all anatomical regions as well as for PainNosreg and PainVASreg at baseline and GSI at follow-up ( Table 6).…”
Section: Discussionsupporting
confidence: 88%
“…Such relationships have been found both in chronic pain cohorts and in population-based studies [75][76][77]. These cross-sectional correlations were confirmed in our study and extended also to the longitudinal aspects (Table 5), as we found significant correlations between pain intensities in all anatomical regions as well as for PainNosreg and PainVASreg at baseline and GSI at follow-up ( Table 6).…”
Section: Discussionsupporting
confidence: 88%
“…7,13,22,39,41,51 Such relationships have been found both in chronic pain cohorts and in population-based studies. 4,32,43 In addition, systematic reviews have confirmed evidence for a link between pain and low HRQoL. 32,37 In a systematic review, Leadly et al 32 noted a lack of studies concerning the elderly population.…”
Section: Discussionmentioning
confidence: 92%
“…Past research is consistent with this outcome, indicating that patients undergoing various kinds of back surgery report improvements in levels of anxiety and depression 1 year following the procedure. 17,25 These findings, in correlation with the association of poor mental health and musculoskeletal pain, 7 all provide strong evidence that cervical deformity is q an underlying cause in the depression of its patients. To further understand this model of depression, future research is needed.…”
Section: Figmentioning
confidence: 83%